The Use of Slang In English Songs To Enhance Students’ Vocabularies At MTs Nurul Bahri, Bone Bolango - Paputungan, Nursiti Aisyah; Dai, Sri Oktavia; Maksum, Wilson (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This study aims to analyze the use of slang in English songs as a means to improve students' vocabulary at MTs Nurul Bahri, Bone Bolango. The phenomenon of using slang in English songs is increasingly popular among teenagers, but its understanding and application in the context of foreign language learning has not been widely explored. This study used a qualitative method with a descriptive approach. Data were collected through analysis of song lyrics containing slang, as well as interviews with 24 students in VIII grades and teachers to find out the impact of slang use on vocabulary improvement. The results show that the use of slang in English songs can help students in expanding their vocabulary, improve their listening skills, and motivate them to be more interested in learning English. In addition, although slang is often not found in formal dictionaries, an understanding of the proper use of slang can add value to students' language skills in social and cultural contexts. This study suggests that the use of English songs containing slang can be integrated in English learning at school to improve students' language skills in a more contextual and interesting way.